Examining the Wind Shear Theory of Sporadic E With ICON/MIGHTI Winds and COSMIC‐2 Radio 2 Occultation Data. Issue 1 (30th December 2021) - Yamazaki, Y.; Arras, C.; Andoh, S.; Miyoshi, Y.; Shinagawa, H.; Harding, B. J.; Englert, C. R.; Immel, T. J.; Sobhkhiz‐Miandehi, S.; Stolle, C.
Abstract: The wind shear theory is widely accepted as an explanation for the formation of a sporadic E (Es) layer, but the direct comparison of Es with the local wind shear has been limited due to the lack of neutral wind measurements. This study examines the role of the vertical wind shear for Es, using signal‐to‐noise ratio profiles from COSMIC‐2 radio occultation measurements and concurrent measurements of neutral wind profiles from the Ionospheric Connection Explorer. It is observed that the Es occurrence rate and average S4 index are correlated with the negative vertical shear of the eastward wind, providing observational support for the wind shear theory. Es can be observed even when the vertical wind shear is positive, which is interpreted as metallic ion layers generated at an earlier time. Plain Language Summary: Sporadic E (Es) is anomalous radio propagation resulting from intense clouds of ionization at heights of the E‐region ionosphere (90–120 km). The formation of an Es layer is generally attributed to the vertical wind shear, which can move metallic ions in the vertical direction by the Lorentz force. According to the wind shear theory, a negative shear of the eastward wind is effective in converging the metallic ions into a thin layer to produce Es. Although previous observations and modeling studies have supported the theory to various degrees, the direct comparison of Es with the vertical wind shear has been limited due to sparse observations of neutral winds at E‐region heights. Neutral wind profiles from the Ionospheric Connection Explorer mission, together with Es data from COSMIC‐2 radio occultation measurements, provide an opportunity to fill this knowledge gap. Direct comparisons of these measurements reveal that the Es occurrence rate is higher and lower for larger negative and positive wind shears, respectively, providing observational evidence for the wind shear theory. Key Points: Conjunction observations of sporadic E (Es) from COSMIC‐2 and neutral wind profiles from Ionospheric Connection Explorer/Michelson Interferometer for Global High‐Resolution Thermospheric Imaging are analyzed Es occurrence rate correlates with the negative vertical shear of eastward wind, providing observational evidence for the wind shear theory Es can be observed even when the vertical shear of the local eastward wind is positive